Synthesis of a feedforward control system for object with distributed parameters - Bochkareva, Irina S.; Tychinina, Yuliya A.; Tychinin, Aleksandr V. (Vestnik of Samara State Technical University. Technical Sciences Series, 2023)
This study is researching a synthesis of an automatic control system for maintaining the temperature of petroleum products during storage in tanks. A new approach for the system construction has been developed during this research. It helps to get rid of disadvantages of existing methods of heating tanks. Developed control system is built on the basis of the feedforward control principle. The object of control is the tank insulation layer, considered as an object with distributed parameters, which provides opportunity to take into account the high inertia of the object. The uneven distribution of temperature is taken into account only over the thickness of the thermal insulation layer, thus, when modeling the control object, a linear one-dimensional heat conduction equation was used, supplemented by initial and boundary conditions of the third kind. To ensure invariance to a disturbing effect in the form of a negative ambient temperature, a compensation element is built using the method of periodic structures. The required heating power dynamics of the heating cable is calculated to compensate for heat losses by the compensation element, depending on the current ambient temperature. Result of this study is a high-performance system that allows maintaining the high precision temperature of the oil in the tank. The article also provides research of the periodic structure parameters impact on the quality of the control algorithm.